Formulasi Obat Kumur Ekstrak Kulit Nanas sebagai Antibakteri Streptococcus mutans - Kony Putriani; Senti Dwi Suryani; Nadya Putri Auliya Serawaidi; Nur Izzati (Poltekkes Kemenkes Riau, 2026)
Dental caries is an oral health problem that is caused by Streptococcus mutans. Pineapple peel is known to contain bioactive compounds such as flavonoids, tannins, saponins, phenolics, and bromelain, which have potential antibacterial properties. This study aimed to formulate an ethanol extract of pineapple peel into a mouthwash preparation and to evaluate its antibacterial activity against Streptococcus mutans. This research used an experimental laboratory method with the disc diffusion technique. The extract concentrations used were 5%, 10%, and 15%, which were then formulated into mouthwash preparations F1, F2, and F3. The evaluation of the formulations included organoleptic tests, pH, viscosity, and antibacterial activity. The results showed that the ethanol extract of pineapple peel at concentrations of 5%, 10%, and 15% produced inhibition zones of 12.1±1.05 mm, 12.0±1.00 mm, and 13.4±1.64 mm, respectively. Meanwhile, the mouthwash formulations F1, F2, and F3 produced inhibition zones of 11.1±0.1 mm, 11.5±1.2 mm, and 11.2±0.76 mm, respectively. ANOVA test results indicated a significant difference among treatments (p < 0.05). It can be concluded that the ethanol extract of pineapple peel formulated as a mouthwash exhibits strong antibacterial activity against Streptococcus mutans